Application of a ventilation fan-misting bank on pigs kept in a stationary trailer before unloading: Effects on trailer microclimate, and pig behaviour and physiological response - Pereira, T. L.; Titto, E. A. L.; Conte, S.; Devillers, N.; Sommavilla, R.; Diesel, T.; Dalla Costa, F. A. [UNESP]; Guay, F.; Friendship, R.; Crowe, T.; Faucitano, L. (Elsevier B.V., 2018)
The aim of this study was to evaluate the effectiveness of water misting with forced ventilation on a stationary trailer on internal vehicle ambient conditions, and behavioural and physiological response of market pigs. During 6 shipments, two identical 2-axle pot-belly trailers transported 191 pigs each (126 +/- 5 kg BW) to the same slaughter plant (135 km). On arrival, trailers were kept stationary in the yard for 30 min before unloading. One trailer was positioned along a fan-misting bank (PBVM), while the other trailer had no access to this cooling system (PBC). The PBVM treatment consisted of 10 min of fan-assisted ventilation (phase 1, P1) followed by 10 min of ventilation and water misting (phase 2, P2) and a final 10 min of ventilation (phase 3, P3). Within each trailer, 4 compartments (rear-top [C4], front-middle [C5], center-middle [C7], and front-bottom [C9]) were chosen for data collection. The air temperature (T) and relative humidity (RH) were monitored using data loggers. The percentage of lying pigs during each phase, and the latency to lie down and the frequency of drinking during lairage were calculated. Gastrointestinal tract temperature (GTE) and exsanguination blood lactate, hematocrit, creatine kinase and cortisol concentrations were assessed. Data from the last 5 min of P1 (wait 1), P2 (wait 2), and P3 (wait 3) were analysed. In wait 1, the application of the fan-assisted ventilation resulted in lower (P <= 0.05) T and temperature-humidity index (THI) in the PBVM compared to the PBC. A greater (P 0.05) drop in RH was recorded in C5 and C7 of the PBVM compared to the same compartments in the PBC. In wait 3, T and THI were lower (P < 0.001) in PBVM compared to PBC, but the RH was higher (P < 0.01). Pigs from C4 in the PBVM had a greater (P < 0.001) activity during phases 2 and 3, and a reduced latency to lie down in the lairage pen compared to the same compartment in the PBC (P <= 0.05). A higher (P <= 0.05) GTT drop was recorded until 1 h after lairage in pigs located in PBC compared to those transported in PBVM. Although the efficiency of the fan-misting bank varied by compartment location, this cooling system appears to be effective in improving the trailer internal thermal environment and thermal comfort of pigs kept in a stationary trailer.
Keywords: Behaviour; Blood metabolites; Cooling system; Gastrointestinal tract temperature; Pigs; Transport